Historiek van de Rijksnormaalschool Hasselt 1955-56 - 1966-67 - Weytjens, G.; Trouvé, R. (Hasselt : Rijksnormaalschool Hasselt, 1967)
Bibliotheek Camille Huysmans
Nederlands
Brochure
Keywords: gemeenschapsonderwijs; Hasselt